Positioning Youth in Maintaining the Mandarese Language - Adawiah, Rabiatul; Marliana, Rina; Nasrah, Nasrah; Husna, Asmaul (Inspiring: English Education Journal, 2024)
Youth is the potential speaker in the future and plays a significant role in language maintenance and vitality. This study aims to investigate the role, attitude, and language skills of Mandarese youth in maintaining their local language. It applied quantitative research and involved five representatives from eighteen districts in Polewali Mandar regency. The results indicate that the youth's role in preserving Mandarese culture, including its language and ability to use it, is deteriorating. The average percentage of their proficiency in the Mandarese language is 48.5%, while the percentage for the actual role is 27.5%. However, given that the youth still have a positive attitude toward that language, which is approximately 78.75% on average, the effort to save Mandarese from the definitively endangered situation is possible.